Application of the shrinking-core model to the kinetics of repeated formation of methane hydrates in a system of mixed dry-water and porous hydrogel particulates - Shi, B.; Fan, S.; Lou, Xia (Pergamon, 2014)
Mixed dry-water (DW) droplets and porous hydrogel (HYD) microspheres have been investigated for applications in reversible methane storage in the form of clathrates. The process of the methane hydrates formation in the presence of these particles was found to be complex. In this work, a modified shrinking-core model was used to simulate the process and to extract the diffusivity and the adsorption rate constant of methane based on the experimental data. The results indicated that the formation of methane hydrates in the mixed particulate systems was affected by water molecules from three different sources: the DW droplets, the HYD particles and the free water (FW) present in the system. The extracted value of initial methane diffusivity, Df0,DW (1.35×10−7–0.99×10−7 m2/s) for DW droplets, and Df0,HYD (1.59×10−7–5.24×10−7 m2/s) for HYD particles, are three orders of magnitude greater than that of bulk water (5×10−12 to 5×10−10 m2/s). The adsorption rate constant of methane, K⁎HYD (0.55×10−5–5.81×10−5 mol/m2 s MPa) of HYD particles, and K⁎DW (5.49×10−6–6.05×10−6 mol/m2 s MPa) of DW droplets, also are greater than the reported value of stirred bulk water (5.5×10−6–6.5×10−6 mol/m2 s MPa). The K⁎HYD is 10 times that of K⁎DW when the hydrogel particles are saturated, indicating a favourable design of the scaffold for methane hydrates formation. The results also demonstrated a higher and more stable water conversion yield (90%) in HYD particles, echoing the improved hydrates formation kinetics and better reversibility. The compromised gas capacity in the mixed system was likely due to the presence of a relatively higher volume of FW, which should be prevented in the future design and development of scaffolding materials for clathrates formation.